2016
DOI: 10.1088/1742-6596/724/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Landau quantization and neutron emissions by nuclei in the crust of a magnetar

Abstract: Magnetars are neutron stars endowed with surface magnetic fields of the order of 10 14 − 10 15 G, and with presumably much stronger fields in their interior. As a result of Landau quantization of electron motion, the neutron-drip transition in the crust of a magnetar is shifted to either higher or lower densities depending on the magnetic field strength. The impact of nuclear uncertainties is explored considering the recent series of Brussels-Montreal microscopic nuclear mass models. All these models are based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It has been recently shown that 1 S 0 pairing in pure neutron matter is destroyed if the magnetic field strength exceeds ∼ 10 17 G [109]. Moreover, the magnetic field may also shift the onset of the neutrondrip transition in dense matter to higher or lower densities due to Landau quantization of electron motion thus changing the spatial extent of the superfluid region in magnetar crusts [110,111,112,113].…”
Section: Role Of a High Magnetic Fieldmentioning
confidence: 99%
“…It has been recently shown that 1 S 0 pairing in pure neutron matter is destroyed if the magnetic field strength exceeds ∼ 10 17 G [109]. Moreover, the magnetic field may also shift the onset of the neutrondrip transition in dense matter to higher or lower densities due to Landau quantization of electron motion thus changing the spatial extent of the superfluid region in magnetar crusts [110,111,112,113].…”
Section: Role Of a High Magnetic Fieldmentioning
confidence: 99%
“…For higher magnetic fields, B B rel as measured in SGRs, AXPs, and some radio pulsars, the composition changes depending on the magnetic field strength [6,7,8,9]. In particular, the maximum baryon number densityn max 1 up to which a nuclide (A 1 , Z 1 ) is present exhibit universal quantum oscillations as a function of the magnetic field strength, and increases almost linearly in the strongly quantizing regime [9,10,11]. For comparison, we shall thus consider two extreme situations: i) unmagnetized neutron stars with B ≡ B/B rel = 0, and ii) highlymagnetized neutron stars with a strongly quantizing field B = 2000 (in any region of the outer crust, electrons are confined to the lowest energy level).…”
Section: Model Of the Outer Crustmentioning
confidence: 98%
“…In addition, it was recently shown in Refs. [79,80] that as a result of Landau quantization of electrons' motion under the strong magnetic field of a magnetar, the neutron-drip transition in the crust of the star is shifted to either higher or lower densities depending on the magnetic field strength. The quantization of the motion of the electrons also makes the star's crust almost incompressible, leading to a density that remains almost unchanged over a wide range of pressures.…”
Section: With a Power-law Deviationmentioning
confidence: 99%